to trace a path through the dark : on forming bodies to see through, and be seen by : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Te Whanganui-a-Tara, Aotearoa - Whitta, Belinda (Massey University, 2024)
to trace a path through the dark is a photographic performance incorporating two analogue slide projectors side by side, which I control manually standing between them. The left hand projector casts abstract, cameraless images produced through a ritual of burying photographic film in a hole in the ground at night. These earthly portraits are projected alongside haptic photographs which communicate my experiences of the ritual and my subsequent evolving relationship with land farmed by my settler-colonial ancestors. The performance occurs in a room darkened by mud applied onto the windows. I operate both the slide projectors with remotes attached to the projectors via cords, sequentially revealing the photographs, forming a conversation between the earthly portraits and haptic photographs. The performance is accompanied by a soundtrack composed of layered recordings made during the journey to the site where I bury film. Alongside the soundtrack is a periodic spoken word element inspired by experiences making the photographic work in the dark. My voice is amplified from behind the audience, who are facing towards the screens and the speakers that play the soundtrack forming another conversation that the audience are positioned within. to trace a path through the dark is a carefully collected set of experiences which, through performance, draw the audience into the rituals of my making.
Figures are reproduced with permission.
Keywords: 360603 Performance art; 360604 Photography, video and lens-based practice